2022
DOI: 10.1021/acs.orglett.2c01657
|View full text |Cite
|
Sign up to set email alerts
|

A Bi(OTf)3-Promoted Hydrosulfonylation of Alkenes with Sulfonyl Hydrazides: An Approach to Branched Sulfones

Abstract: The Bi­(OTf)3-promoted hydrosulfonylation of alkenes with sulfonyl hydrazides to produce branched sulfones is reported, in which various branched sulfones (>40 examples) have been prepared in moderate to good yields. The gram-scale reaction and synthesis of the experimental inhibitor precursor showed the potential application. A preliminary mechanistic study revealed that double-bond migration to form the α,β-conjugated alkene is crucial for this transformation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…Among them, sulfonyl hydrazines 2a , 2d , 2g – 2k , 2t , and 2w are commercially available. Other substrates ( 2b , 2c , 2e , 2f , 2l – 2s , 2u , 2v , 2x , and 2y ) are known, and the spectroscopic and physical data are completely matched with those from the literature …”
Section: Methodsmentioning
confidence: 92%
“…Among them, sulfonyl hydrazines 2a , 2d , 2g – 2k , 2t , and 2w are commercially available. Other substrates ( 2b , 2c , 2e , 2f , 2l – 2s , 2u , 2v , 2x , and 2y ) are known, and the spectroscopic and physical data are completely matched with those from the literature …”
Section: Methodsmentioning
confidence: 92%
“…Engle and co-workers reported a regiocontrolled hydroamination reaction of inactive olefins compatible with a range of nitrogen nucleophiles, though the 8-aminoquinoline directing group was the key to reaction success (Scheme b) . Engle, Fu, and our group have demonstrated that 3-butenoic acid is synthetically important and produces various important organic molecules.…”
Section: Introductionmentioning
confidence: 99%
“…Although substantial efforts have been made to install SO 2 units in organic scaffolds, [11] there has been less success in constructing branched sulfones. [12] In this regard, Xu et al reported a protocol involving copper catalysis to synthesize β-keto thiosulfones by utilizing styrenes and PhSO 2 SR as coupling partners in acetonitrile. [13] Recently, Wang and co-workers developed a chemoselective insertion methodology (Scheme 1C) using pre-functionalized sulfoxonium ylides and thiosulfonates at 100 °C in dimethyl sulfoxide (DMSO).…”
Section: Introductionmentioning
confidence: 99%
“…Herein, we disclose an I 2 ‐catalyzed straightforward approach towards β ‐keto sulfones using methyl ketones and sulfonyl hydrazides in a step‐efficient manner under solvent‐free conditions. Although substantial efforts have been made to install SO 2 units in organic scaffolds, [11] there has been less success in constructing branched sulfones [12] . In this regard, Xu et al .…”
Section: Introductionmentioning
confidence: 99%